A Review on Introduction, Importance and Applications of Peptidomimetics. - Patil Kunal; Chaudhari Anwar; Dule Priya; Garkar Rushikesh; Sayais Prashant; Patil Rutik; Jagtap Vaibhav kumar (Asian Journal of Pharmaceutical Research and Development, 2024)
Peptidomimetics, a class of compounds that bridge the gap between peptides and small molecules, have emerged as a transformative class of compounds in drug discovery and therapeutics. Using information from recent studies, this review examines the importance, design approaches, uses, and potential future directions of Peptidomimetic When compared to natural peptides, peptidomimetics show superior stability, selectivity, and versatility. This increases the drug gable space and makes it possible to develop novel therapeutic modalities. Optimizing the pharmacokinetic properties and target interactions of peptidomimetics requires the application of rational design strategies, structural modifications, and synthetic methodologies. Targeting protein-protein inter actions, inhibiting enzymes, and modifying immune checkpoints are examples of diverse therapeutic applications with potential in oncology, infectious diseases, neurology, and other fields. It is the goal of future research directions to embrace interdisciplinary approaches, investigate cutting-edge fields like immunotherapy and precision medicine, and address issues like off-target effects and synthetic accessibility. Peptidomimetics has the potential to significantly transform drug discovery and advance precision medicine techniques for better patient outcomes.